Analysing drivers and outcomes of job and professional satisfaction at health centres in Portugal - Santana, S.; Loureiro, S. M. C. (Benchmarking: An International Journal, 2019)
Purpose The objective of the study was to analyse antecedents, associations and outcomes of job and professional satisfaction of doctors and nurses in Portuguese health centres. Methods We have used structural equation modeling (SEM) to examine the causal relationships between multiple variables placed in a path model reflecting the theoretical foundation. Findings The percentage of those satisfied or very satisfied with their jobs were just above 50%. Doctors’satisfaction stems from personal achievement and the formal component of work environment,leading them to strongly recommend their work in the health centre to dear ones but not to put aside other job options. Nurses’ level of job satisfaction seems to be affected by co-workers and interpersonal relationships beside personal achievement and have more strong and multifaceted impact on their feelings and behaviour, that goes from recommending their job position, to consider job quit and even regretting the option made in terms